THE URGENCY OF BUILDING LEGAL AWARENESS IN THE BOND OF LOVE IN YOUTH - Suud Sarim Karimullah (PPKn, Fakultas Keguruan dan Ilmu Pengetahuan Universitas Palangka Raya, 2022)
This research aims to educate youths on the importance of building legal awareness of courtship relationships in the bond of love. Then, the literature analysis is used to approach this research, which relates to violations and violence in a love relationship among adolescents, to obtain an overview of legal phenomena through an analysis presented in a descriptive-analytic manner through several qualitative procedures. Furthermore, the results of this study state that an understanding of the law among teenagers in the bond of love through courtship relationships is a fundamental matter to be given, especially with the increasing number of irregularities and violations that occur in courtship relationships among these teenagers. Understanding the law in adolescents requires adjustment to its development, so a strategic step is needed to maintain a good relationship with a partner healthily without any violations or violence.